Relationship Between Interpretation, Alliance, and Outcome in Psychodynamic Psychotherapy. Issue 6 (June 2015) - Levy, Saryn R.; Hilsenroth, Mark J.; Owen, Jesse J.
<x xml:space="preserve">Abstract</x> Abstract The current study examines the relationship between therapist interpretations in the early stages of psychodynamic psychotherapy and subsequent outcomes for 76 outpatients. Pre-treatment characteristics of global symptomatology, personality pathology, insight, and level of object relations were examined as possible significant patient characteristics. Independent clinicians reliably rated therapist use of interpretations over two early treatment sessions (third and ninth). Patient-rated alliance was also examined as a possible psychotherapy process predictor of change. Therapy outcomes were measured based on patients' changes in global symptomatology and estimates of improvement across a broad range of functioning at the end of treatment. An examination of the study independent variables revealed significant relationships between pre-treatment personality disorder symptomatology with patient object relations (OR), patient OR with pre-treatment insight, and pre-treatment insight with use of therapist interpretation. Pre-treatment symptomatology and early treatment interpretations predicted reliable change in global symptomatology. Patients' estimates of improvement across a broad band of functioning were most significantly impacted by quality of alliance. Analysis of these outcome relationships controlled for therapist effects. Statistical implications of therapist effects are discussed in regard to this area of research and future directions for investigation are explored.